2014
DOI: 10.1039/c4cc01835d
|View full text |Cite
|
Sign up to set email alerts
|

Unusual redox stability of neptunium in the ionic liquid [Hbet][Tf2N]

Abstract: The behavior of neptunium in the ionic liquid betaine bistriflimide, [Hbet][Tf2N], has been studied spectroscopically at room temperature and 60 °C for the first time. An unprecedented complex redox chemistry is observed, with up to three oxidation states (iv, v and vi) and up to six Np species existing simultaneously. Both redox reactions and coordination of betaine are observed for Np(iv), (v) and (vi). Elevating the temperature accelerates the coordination of Np(v) with betaine and reduction reactions slow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…This indicated that betaine and [Hbet]­[Tf 2 N] have a higher affinity for scandium than for the other rare-earth elements. Sasaki et al applied the ionic liquid [Hbet]­[Tf 2 N] for the selective extraction of uranium and the precious metals palladium, rhodium, and ruthenium. , Other authors have investigated the coordination chemistry of f-block elements in [Hbet]­[Tf 2 N]. On the basis of the difference in affinity between scandium and the lanthanides, [Hbet]­[Tf 2 N] is applied in this paper to the selective extraction of scandium­(III) from rare-earth mixtures. Furthermore, the extraction behavior of the ionic liquid toward the major metal ions present in red mud leachates is examined, namely, Fe­(III), Al­(III), Ti­(IV), Ca­(II), and Na­(I), to evaluate whether [Hbet]­[Tf 2 N] is suitable for the selective recovery of Sc­(III) from red mud leachates.…”
Section: Introductionmentioning
confidence: 99%
“…This indicated that betaine and [Hbet]­[Tf 2 N] have a higher affinity for scandium than for the other rare-earth elements. Sasaki et al applied the ionic liquid [Hbet]­[Tf 2 N] for the selective extraction of uranium and the precious metals palladium, rhodium, and ruthenium. , Other authors have investigated the coordination chemistry of f-block elements in [Hbet]­[Tf 2 N]. On the basis of the difference in affinity between scandium and the lanthanides, [Hbet]­[Tf 2 N] is applied in this paper to the selective extraction of scandium­(III) from rare-earth mixtures. Furthermore, the extraction behavior of the ionic liquid toward the major metal ions present in red mud leachates is examined, namely, Fe­(III), Al­(III), Ti­(IV), Ca­(II), and Na­(I), to evaluate whether [Hbet]­[Tf 2 N] is suitable for the selective recovery of Sc­(III) from red mud leachates.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27][28][29][30] The liquid-liquid extraction of Ln/An using RTILs as a solvent 21,26,29,31 and/or direct dissolution of Ln/An oxides in the RTIL 25,28,[32][33][34][35][36] has gained popularity in the recent past. 31,35,37 Although there are several reports available on the U(VI) ion stability, complexation and speciation in RTILs, [38][39][40] there is no report on the Np(v) speciation in a hydrophobic RTIL except one recently published by Dong et al 41 The unusual stability of the different oxidation states of Np in a hydrophilic RTIL (namely Hbet.NTf 2 ) was reported by Long et al 42 A hydrolysis-stable complex of Np(IV), i.e., [BuMeIm] 2 [NpCl 6 ] (where BuMeIm + is 1-n-butyl-3-methylimidazolium) in a hydrophobic RTIL 43 was reported by Nikitenko et al 43 Although the Np(V) f-f transition peak position and the associated e value are known for the aqueous media, only one report is available on the complexation of Np(V) with nitrate in RTIL. 41 Our earlier studies for CCI of Np(V) with the other actinides such as U(VI) 12 or Th(IV) 11 suggested that the CCI of Np(V) with other actinides, such as U(VI) was weak and electrostatic in nature and hence, should be very much affected by the medium.…”
Section: Introductionmentioning
confidence: 72%
“…2,3,6,44 Long et al have reported a single sharp peak centred at 980 nm for Np(V) in water-saturated Hbet.NTf 2 . 42 The spectra of Np(V) in water, wet RTIL and dry RTIL are recorded in the present study to understand any changes in the symmetry or local coordination around the Np(V) ion or any redox transformation in these media.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation